Relationship Between Diversification Strategy Applications And Organizational Performance According To Herfindahl Index Criteria - YİĞİT, İHSAN (ELSEVIER SCIENCE BV, 2012)
In Turkish literature it has been obseved that there is only a single study by using Rumelt's diversification index in order to explain the diversification strategy-organizational prformance relationship. Herfindahl index of diversification differed in many respects from Rumelt's index of diversification. Rumelt's index handles diversification in four groups as concentrated, main business based, related and unrelated. However Herfindahl Index grades the diversification as relateed, unrelated and for the total diversification in itself separately. By using diversification - organizational performance relationship on the basis of Herfindahl Index, the data of the balance sheets of the enterprises listed to the Istanbul Stock Exchange were received from the addresses www.kap.gov.tr and www.imkb.gov.tr. ROA and ROS values used as performance criteria have been obtained from balance sheet and income statements. The result that Herfindahl based diversification strategy applications and organizational performance relationship differ in the developed countries, but similar results in the developing countries were obtained at the end of the study.
Keywords: Diversification strategy; organizational perfomance; diversification strategy in the emerging market; Herfindahl Index; CORPORATE DIVERSIFICATION; TECHNOLOGICAL DIVERSIFICATION; EMERGING MARKETS; BUSINESS GROUPS; FIRMS